2015
DOI: 10.1038/ncomms7392
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous monoliths of inverse bicontinuous cubic phases of block copolymer bilayers

Abstract: Solution self-assembly of block copolymers into inverse bicontinuous cubic mesophases is a promising new approach for creating porous polymer films and monoliths with highly organized bicontinuous mesoporous networks. Here we report the direct self-assembly of block copolymers with branched hydrophilic blocks into large monoliths consisting of the inverse bicontinuous cubic structures of the block copolymer bilayer. We suggest a facile and scalable method of solution self-assembly by diffusion of water to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 50 publications
0
55
0
Order By: Relevance
“…[18] This method, the solvent-diffusion/ evaporation-mediated self-assembly (SDEMS) of BCPs,a llowed the solution self-assembly of bPEG-PS n on as tationary substrate under static conditions (see SI for ad etailed procedure). [18] This method, the solvent-diffusion/ evaporation-mediated self-assembly (SDEMS) of BCPs,a llowed the solution self-assembly of bPEG-PS n on as tationary substrate under static conditions (see SI for ad etailed procedure).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 3 more Smart Citations
“…[18] This method, the solvent-diffusion/ evaporation-mediated self-assembly (SDEMS) of BCPs,a llowed the solution self-assembly of bPEG-PS n on as tationary substrate under static conditions (see SI for ad etailed procedure). [18] This method, the solvent-diffusion/ evaporation-mediated self-assembly (SDEMS) of BCPs,a llowed the solution self-assembly of bPEG-PS n on as tationary substrate under static conditions (see SI for ad etailed procedure).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…

We report here as trategy for influencing the phase and lattice of the inverse mesophases of as ingle branchedlinear block copolymer (BCP) in solution which does not require changing the structure of the BCP.T he phase of the self-assembled structures of the blockc opolymer can be controlled ranging from bilayer structures of positive curvature (polymersomes) to inverse mesophases (triply periodic minimal surfaces and inverse hexagonal structures) by adjusting the solvent used for self-assembly.B yu sing solvent mixtures to dissolve the blockc opolymer we were able to systematically change the affinity of the solvent towardthe polystyrene block, which resulted in the formation of inverse mesophases with the desired lattice by self-assembly of as ingle branched-linear blockc opolymer.O ur method was also applied to an ew solution self-assembly method for ab ranched-linear block copolymer on as tationary substrate under humidity,w hich resulted in the formation of large mesoporous films.O ur results constitute the first controlled transition of the inverse mesophases of blockc opolymers by adjusting the solvent composition.

The direct self-assembly of amphiphilic block copolymers (BCPs) into inverse bicontinuous structures in solution is an emerging strategy for creating highly ordered porous polymers with three-dimensionally interconnected networks of large pores. [1][2][3][4][5][6][7][16][17][18][19] We recently reported that diblock copolymers,composed of adendritic or branched hydrophilic block and ahydrophobic linear polymer block, preferentially self-assemble into triply periodic minimal surfaces (TPMSs) of the BCP bilayers in solution, resulting in the creation of polymer cubosomes having highly defined internal large-pore networks. [1][2][3][4][5][6][7][16][17][18][19] We recently reported that diblock copolymers,composed of adendritic or branched hydrophilic block and ahydrophobic linear polymer block, preferentially self-assemble into triply periodic minimal surfaces (TPMSs) of the BCP bilayers in solution, resulting in the creation of polymer cubosomes having highly defined internal large-pore networks.

…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular importance is the ability to obtain accurate and reproducible control over the reaction conditions such as temperature, pressure and reaction solvent. [9,11] Furthermore, monolithic devices (microreactors containing a porous network of typically silica or other oxide materials) can be functionalized extensively with enzymes [12], magnetic nanoparticles [11] and other functional groups [12][13][14] in order to tailor their catalytic properties such as selectivity and activity. [10,15].…”
Section: Introductionmentioning
confidence: 99%